2020
DOI: 10.22270/jddt.v10i2-s.3963
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Pro-Inflammatory Molecules by Ginger (Zingiber officinale Roscoe) and its Anti-Inflammatory Effects on Arthritis Patients

Abstract: Herbal medicinal plants are used to treat various disorders in many traditional medicinal systems around the world. Usage of this herb found in Indian and Chinese medicinal systems. The availability of ginger herb is Universal these days, where it is cultivated for its underground stem (Pseudo-stem). Most commonly used part is rhizome. This  ginger rhizome has many therapeutic uses including anti-inflammatory, anti-diabetics, antioxidant, anti-microbial and also curing in vomiting, constipation, indigestion, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Another interesting study by Mutthuraj and co-workers (2020) found that topical application of ginger essential oil on patients suffering from arthritis for 30 days inhibited the proinflammatory molecules by reducing the serum levels of rheumatoid arthritis (RA) factor, C reactive protein (CPR), and erythrocyte sedimentation rate (ESR). These results suggest that ginger has pungent anti-inflammatory potential, which can be used in the treatment of joint pain and swelling (Mutthuraj et al, 2020).…”
Section: Clinical Studiesmentioning
confidence: 79%
See 1 more Smart Citation
“…Another interesting study by Mutthuraj and co-workers (2020) found that topical application of ginger essential oil on patients suffering from arthritis for 30 days inhibited the proinflammatory molecules by reducing the serum levels of rheumatoid arthritis (RA) factor, C reactive protein (CPR), and erythrocyte sedimentation rate (ESR). These results suggest that ginger has pungent anti-inflammatory potential, which can be used in the treatment of joint pain and swelling (Mutthuraj et al, 2020).…”
Section: Clinical Studiesmentioning
confidence: 79%
“…The increase in levels of inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), IL-1β, and IL-6, play an essential role in rheumatoid arthritis (Bode and Dong, 2011;Aryaeian et al, 2019). It has been reported that 6-gingerol and 6-shogaol attenuate the production of pro-inflammatory molecules such as prostaglandins by suppressing the enzymes cyclooxygenase (COX)-1 and COX-2 (Grzanna et al, 2005;Saptarini et al, 2013;Mutthuraj et al, 2020).…”
Section: Anti-inflammatory Activitiesmentioning
confidence: 99%
“…O 6-Gingerol é o principal composto ativo do gengibre, responsável pelas propriedades anti-inflamatórias, antioxidantes, gastroproteção, anti-artrite, analgésicas e antipiréticas. Também possui ação antiemética, antimicrobiana, antitrombótica, inibindo a agregação plaquetária além de atuar no sistema imunológico estimulando-o [6,12] . O gengibre é utilizado popularmente como chá preparado por infusão, considerando a quantidade de 0,5-1 g de rizomas secos de Z. officinale na proporção de 150 mL de água.…”
Section: Zingiber Officinale Roscoeunclassified
“…ZO also confers a crucial inflammatory effect. It was reported that ginger essential oil extract could reduce the pro-inflammatory molecules to attenuate arthritis by lowering rheumatoid arthritis factor, C-reactive protein, and erythrocyte sedimentation rate level in the blood ( 18 ). Additionally, Cakir et al ( 10 ) reported that ZOEOs showed positive effects on treatment and prevention of necrotizing enterocolitis via inhibiting inflammatory factors such as IL-6, P65 and COX-2.…”
Section: Introductionmentioning
confidence: 99%